2002
DOI: 10.1021/jp020785q
|View full text |Cite
|
Sign up to set email alerts
|

Coulostatic Potential Transients Induced by Laser Heating of a Pt(111) Single-Crystal Electrode in Aqueous Acid Solutions. Rate of Hydrogen Adsorption and Potential of Maximum Entropy

Abstract: Short pulses (∼10 ns) of high-power laser light produce a sudden increase in the surface temperature of a Pt(111) single-crystal electrode in acidified potassium perchlorate or sulfate solutions. The change of the electrode potential at open circuit was monitored during the relaxation of the temperature. At low pH, the potential transients in the hydrogen adsorption region exhibit a bipolar shape, which can be explained considering that the relaxation is influenced by the rate of hydrogen adsorption. With this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
153
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(172 citation statements)
references
References 45 publications
19
153
0
Order By: Relevance
“…With this information it could be concluded that pzfc and pztc almost coincided in the case of Pt(111) with a value of 0.32 V SHE. This value agrees reasonable well with the position where water dipole reorientation is inferred from IR measurements [33] and laser induced temperature jump experiments [34,40]. A maximum in the differential capacity has been indeed interpreted as a consequence of dipole reorientation [32], although in this case, it was proposed that the pzfc does not coincide with the peak but it is located at higher potentials, in the OH adsorption region.…”
Section: 1charge Evaluationsupporting
confidence: 85%
See 1 more Smart Citation
“…With this information it could be concluded that pzfc and pztc almost coincided in the case of Pt(111) with a value of 0.32 V SHE. This value agrees reasonable well with the position where water dipole reorientation is inferred from IR measurements [33] and laser induced temperature jump experiments [34,40]. A maximum in the differential capacity has been indeed interpreted as a consequence of dipole reorientation [32], although in this case, it was proposed that the pzfc does not coincide with the peak but it is located at higher potentials, in the OH adsorption region.…”
Section: 1charge Evaluationsupporting
confidence: 85%
“…Alternatively, the position of the pzfc can be inferred from indirect measurements, like the reorientation of water dipoles as monitored with infrared spectroscopy [33] or laser inducted temperature jump measurements [34][35][36][37][38][39][40][41]. It is also worth mentioning in this context the studies in UHV of model double layer systems created by sequential dosing of the same components of the true double layer in electrochemical environment [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the previous description, thermodynamic considerations demonstrate that the thermal coefficient of the potential drop is linked with the entropy of double layer formation through [32,33,35,36]:…”
Section: E V Vs Shementioning
confidence: 90%
“…The change in the open circuit potential during a change of temperature induced by pulsed laser irradiation can be rationalised considering that the main contribution comes from the perturbation of the dipolar part of the potential drop [32][33][34][35]. Such dipolar contribution will be negative for positive electrode charges, since, in this case, the water dipoles will be oriented with the oxygen towards the metal adding a negative term to the potential difference  M - S .…”
Section: E V Vs Shementioning
confidence: 99%
See 1 more Smart Citation